2013
DOI: 10.1128/genomea.00817-13
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Bacillus thuringiensis var. thuringiensis Strain T01-328, a Brazilian Isolate That Produces a Soluble Pesticide Protein, Cry1Ia

Abstract: Bacillus thuringiensis var. thuringiensis strain T01-328, isolated from Cubatão county (São Paulo State, Brazil), produces a soluble pesticide protein, Cry1Ia, during vegetative growth. Here, we report the 7.089-Mbp draft genome sequence, composed of a 5.5-Mb chromosome and 14 plasmids, which is the largest B. thuringiensis genome sequenced to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…And the following PCR detection experiment using primers specific for each of the genes confirmed our speculation ( Figure 5 ). On the other hand, the Cry1Ia protein was a secreted delta-endotoxin produced by several Bt strains during vegetative growth and could not form a classic crystal like other Cry proteins ( Dammak et al, 2011 ; Varani et al, 2013 ). Thus, it was not surprising that Cry1Ia and Vip3A proteins were not detected during the spore-release period of X022.…”
Section: Discussionmentioning
confidence: 99%
“…And the following PCR detection experiment using primers specific for each of the genes confirmed our speculation ( Figure 5 ). On the other hand, the Cry1Ia protein was a secreted delta-endotoxin produced by several Bt strains during vegetative growth and could not form a classic crystal like other Cry proteins ( Dammak et al, 2011 ; Varani et al, 2013 ). Thus, it was not surprising that Cry1Ia and Vip3A proteins were not detected during the spore-release period of X022.…”
Section: Discussionmentioning
confidence: 99%
“…Masson et al [77] observed that the encoded Cry1I protein did not accumulate in crystals in Bt strain HD-133 [78,79]. The Cry1I protein therefore could not be found in the bacterial cell after the T5 sporulation stage [80,81].…”
Section: No Known Crystallization Factorsmentioning
confidence: 99%